Characterization of Sv129 Mice as a Susceptible Model to Leishmania amazonensis - dos-Santos, Júlio Souza; Firmino-Cruz, Luan; Ramos, Tadeu Diniz; Fonseca-Martins, Alessandra Marcia da; Oliveira-Maciel, Diogo; De-Medeiros, Juliana Valente Rodrigues; Chaves, Suzana Passos; Gomes, Daniel Claudio Oliveira; de Matos Guedes, Herbert Leonel (Frontiers in Medicine, 2019)
Leishmaniasis is a complex of neglected diseases caused by parasites of the genus Leishmania, such as Leishmania (Leishmania) amazonensis, the ethiologic agent of diffuse cutaneous leishmaniasis in Brazil. In this work, we investigated a new experimental model of infection for L. amazonensis: the Sv129 mouse. First, we subcutaneously infected Sv129 mice with 2x105 or 2x106 L. amazonensis parasites of the Josefa strain. A progressive lesion developed for both inoculation doses, showing that Sv129 mice are susceptible, independent of parasite dose. We next investigated the mechanisms associated with the pathogenesis of infection. We did not observe an increase of frequency of interferon-gamma (IFN- γ)-producing CD4+ and CD8+ T cells, a phenotype similar to that seen in BALB/c mice. There was an increased of frequency and number of IL-17-producing γδ (gamma-delta) T cells in infected Sv129 mice compared to naïve SV129 and an increased frequency of this population compared to infected BALB/c mice. In addition, Sv129 mice presented high levels of both IgG1 and IgG2a, suggesting a mixed Th1 and Th2 response with a skew towards IgG1 production based on IgG1/IgG2a ratio. Susceptibility of the Sv129 mice was further confirmed with the use of another strain of L. amazonensis, LTB0016. In this work, we characterized the Sv129 mice as a new model of susceptibility to Leishmania amazonensis infection, during infection there was controlled IFN-γ production by CD4+ or CD8+ T cells and induced IL-17 production by γδ T cells.